2015
DOI: 10.1002/bab.1426
|View full text |Cite
|
Sign up to set email alerts
|

Simple procedure applying lactose induction and one‐step purification for high‐yield production of rhCIFN

Abstract: Recombinant consensus interferon (CIFN) is a therapeutic protein with molecular weight of 19.5 kDa having broad spectrum antiviral activity. Recombinant human CIFN (rhCIFN) has previously been expressed in Escherichia coli using isopropyl-β-d-thiogalactopyranoside (IPTG), a non-metabolizable and expensive compound, as inducer. For economical and commercial-scale recombinant protein production, it is greatly needed to increase the product yield in a limited time frame to reduce the processing cost. To reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
18
0
2
Order By: Relevance
“…Previously, only plasmid-based expression systems had been subject to studies investigating lactose as an inducer for recombinant protein production [23,36,37]. In those studies, beneficial effects on productivity, cell fitness, viability, and soluble product formation had been reported [21,22,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, only plasmid-based expression systems had been subject to studies investigating lactose as an inducer for recombinant protein production [23,36,37]. In those studies, beneficial effects on productivity, cell fitness, viability, and soluble product formation had been reported [21,22,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…For plasmid-based systems it has been reported that lactose induction provided the advantages of increased soluble product formation and cell fitness [19][20][21][22]. However, as the high specific lactose uptake rates of the GI strain clearly seemed toxic to the cells, we wanted to check if perhaps IPTG induction was beneficial for this strain.…”
Section: Comparison Between Lactose Induction and Iptg Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IPTG is known to put a high metabolic burden on E. coli 910 and is often associated with the generation of misfolded protein aggregates, called inclusion bodies1112. In contrast, the alternative inducer lactose has been shown to favour the production of soluble product and trigger enhanced productivity13141516. Even though lactose metabolism is topic of some recent studies17, lactose is scarcely used in biochemical engineering since induction entails the challenge of continuous supply of the disaccharide as it gets metabolized by E. coli .…”
mentioning
confidence: 99%
“…The refolded protein of the recombinant interleukin‐6 was purified on the AKTA system (GE Healthcare, USA) by using the ion exchange XK26/10 column packed with DEAE Sepharose CL6B. Prior to loading the refolded protein on the column, l ‐arginine and other salts were removed by applying the diafiltration procedure as described . The diafilterd protein was loaded onto the preequilibrated column with 20 cv of the buffer (20 mM sodium phosphate pH 7, 0.01% Tween 20) at the flow rate of 3 mL/Min.…”
Section: Methodsmentioning
confidence: 99%